2014
DOI: 10.1038/ncomms4678
|View full text |Cite
|
Sign up to set email alerts
|

Induction of pluripotency in human somatic cells via a transient state resembling primitive streak-like mesendoderm

Abstract: During mammalian embryonic development, the primitive streak initiates the differentiation of pluripotent epiblast cells into germ layers. Pluripotency can be reacquired in committed somatic cells using a combination of a handful of transcription factors, such as OCT3/4, SOX2, KLF4 and c-MYC (hereafter referred to as OSKM), albeit with low efficiency. Here we show that during OSKM-induced reprogramming towards pluripotency in human cells, intermediate cells transiently show gene expression profiles resembling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
138
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 122 publications
(155 citation statements)
references
References 42 publications
15
138
1
1
Order By: Relevance
“…When ESCs and normal iPSCs differentiated into endoderm (EN), mesoderm (ME), and neuroectoderm (NE), the expression of these markers significantly decreased. However, expression remained high in primitive streak-like mesendoderm (PSMN) (12). Deep sequencing of RNA (RNA-seq) from TRA-1-60 (+) cells exhibited the chimeric transcripts of ABHD12B, HHLA1, C4ORF51, and lincRNA-RoR with LTR7 sequences that meant transcription from intragenic LTR7s of HERV-Hs (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When ESCs and normal iPSCs differentiated into endoderm (EN), mesoderm (ME), and neuroectoderm (NE), the expression of these markers significantly decreased. However, expression remained high in primitive streak-like mesendoderm (PSMN) (12). Deep sequencing of RNA (RNA-seq) from TRA-1-60 (+) cells exhibited the chimeric transcripts of ABHD12B, HHLA1, C4ORF51, and lincRNA-RoR with LTR7 sequences that meant transcription from intragenic LTR7s of HERV-Hs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To this end, we examined LTR7 activities during the course of iPSC generation. We sorted TRA-1-60-positive (+) reprogrammed cells on various days after retroviral transduction of OCT3/4, SOX2, KLF4, and myelocytomatosis oncogene (c-MYC) (subsequently referred to as OSKM) and analyzed their global gene expression by microarrays (11,12). Using principle component analyses (PCA) with the 144 DD-iPSC markers, we found similarities between DD-iPSC subclones and TRA-1-60 (+) intermediate reprogrammed cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4). Indeed, following OSKM transduction in fibroblasts, the expression of mesenchyme-related transcription factors, such as Snai1, Snai2, Twist1, Twist2, Zeb1 and Zeb2, are repressed both in mouse and human cells (Samavarchi-Tehrani et al, 2010;Takahashi et al, 2014). At the same time, mesenchymal-specific surface proteins, Thy1 and Cd44, are repressed (O'Malley et al, 2013).…”
Section: Several Routes To Pluripotency: Mechanisms Of Cell Reprogrammentioning
confidence: 99%
“…R. Soc. B 370: 20140367 dissecting the reprogramming process in mouse [55] and human [56] revealed that the cells in transitional phase are dramatically distinct from both original and fully reprogrammed cells. Because of that iPSC diversity could be due to the epigenetic dynamics during the process of iPSC generation from cells of somatic origin.…”
Section: The Challenges Of Induced Pluripotent Stem Cells (A) Diversimentioning
confidence: 99%